MANAJEMEN PEMBELAJARAN BERBASIS DIGITAL DALAM MENINGKATKAN KETERAMPILAN MEMBACA AL-QUR’AN - Ghulam Al Muntazor, Husen (el-Moona: Jurnal Ilmu Pendidikan Islam, 2024)
First, the skill of reading the Qur'an is an effort to deepen the understanding of Islam, increase faith, and form the moral character of individuals. Reading the Qur'an is not only limited to interpreting letters and words, but involves understanding the meaning of the Qur'an. Efforts to form Qur'anic reading skills are an integral part of Islamic religious education which includes training in tajweed, makhrijul letters, and Nagham Al-Qur'an, manners of reading the Qur'an, and the messages contained in the verses of the Qur'an. Second, digital-based Qur'an learning management includes several aspects including (1) planning including determining learning objectives, designing learning materials, and scheduling learning; (2) organizing includes the management of digital learning platforms and the determination of roles or responsibilities for educators, students and administrators of digital platforms; (3) leadership (leading) includes providing guidance and motivation as well as teacher skills; (4) Supervision (controlling) learning evaluation and monitoring of learning platforms. Third, digital transformation is able to improve the skills of reading the Qur'an. This digital transformation changes the traditional learning paradigm to be modern and innovative. Extensive accessibility through digital devices allows learners to connect with the Qur'an anytime and anywhere.